Oxidation State of Arc Mantle Revealed by Partitioning of V, Sc, and Ti Between Mantle Minerals and Basaltic Melts. Issue 5 (30th May 2019) - Wang, Jintuan; Xiong, Xiaolin; Takahashi, Eiichi; Zhang, Le; Li, Li; Liu, Xingcheng
Abstract: Whether arc mantle is more oxidized than oceanic mantle is persistently debated. The behavior of multivalent vanadium (V) is oxygen fugacity (fO2 ) sensitive, and the ratios of V to a homovalent element (e.g., Sc, Ti, or Yb) in basalts were commonly used as fO2 proxies. Similar ratios, such as V/Sc, between arc basalts and mid‐ocean ridge basalts were previously taken as evidence for similar fO2 s in their mantle sources. However, this claim may be problematic because elemental ratios are primarily controlled by partition coefficients ( D values), which are further affected by various factors. Here we determined D values of V and other transition elements between mantle minerals and basaltic melts at typical arc T–P‐H2 O conditions and variable fO2 s. Combining experimental results with published data, the effects of fO2, T, P, and phase compositions on D V, D Sc, and D Ti for olivine, orthopyroxene (opx), clinopyroxene (cpx), and spinel were evaluated using multiple linear regressions. The results show that D V values for these four minerals all increase with decreasing fO2 and temperature, leading to higher D V / D Sc and D V / D Ti ratios at low temperatures than those at high temperatures given a certain fO2 . Thus, similar V/Sc and V/Ti ratios between arc basalts and mid‐ocean ridge basalts reflect a relatively oxidized arc mantle due to its lower melting temperatures. In light of the highly incompatible behavior of Ti during mantle melting, V‐Ti systematics are regarded to be more superior than V‐Sc systematics in the fO2 estimation. Partial melting modelling results using V‐Ti systematics reveal that arc mantle is, on average, ~0.9 log units higher in fO2 than oceanic mantle. Plain Language Summary: The oxidation state of the Earth`s mantle, often expressed as oxygen fugacity (fO2 ), could control the behavior of multivalent elements and thus exert a significant influence on the formation of magmatic ore deposits and the secular evolution of Earth`s atmosphere. Whether arc mantle is more oxidized than oceanic mantle remains a controversial topic. As a multivalent element, partitioning behavior of vanadium is fO2 sensitive and is capable of tracking mantle redox state. However, except fO2, other factors (temperature, pressure, and phase composition) that may affect vanadium partitioning behavior have not been clearly evaluated. Here we conducted high temperature and pressure experiments to determine partition coefficients of vanadium during mantle melting under various fO2 conditions. Combining our and published data, we evaluated the effects of fO2, T, P, and compositions of mineral and melt on the vanadium partitioning using multiple linear regressions. The results indicate that, in addition to fO2, temperature exerts a significant control on the vanadium partitioning. Additionally, we estimated fO2 of the arc mantle via numerical modelling using appropriate partition coefficients for vanadium. Our results clarify and reconcile the discrepancies between previous studies and reveal that arc mantle is generally ~10 times more oxidized than oceanic mantle. Key Points: In addition to oxygen fugacity, temperature exerts a significant control on V partitioning during mantle melting Considering the temperature effect on V partitioning, similar V/Ti or V/Sc ratios between arc basalts and MORBs indicate a more oxidized arc mantle Modelling results from V‐Ti systematics indicate that arc mantle is ~0.9 log units higher in fO2 than oceanic mantle